Determination of neutron and gamma ray shielding properties, secondary radiation formations and neutron damage of composites containing polyester/pyrite/titanium diboride - Turhan, M. F.; Kacal, M. R.; Ozdogan, H.; Tursucu, A.; Akman, F.; Ogul, H.; Polat, H. (Pergamon-Elsevier Science Ltd, 2025)
Composite materials comprising titanium diboride (TiB2), unsaturated polyester resin, and pyrite (FeS2) at varying weight percentages were fabricated and evaluated for their interaction with neutron and gamma radiation. This study adopts a comprehensive methodology, combining theoretical calculations, experimental measurements, and Monte Carlo simulations using PHITS and MCNP6. A strong correlation was observed among experimental results, WinXCOM data, and simulation outputs, with discrepancies remaining within approximately 5 %. To assess neutron shielding performance, fast neutron removal cross sections and partial neutron transmission rates were determined for both fast and thermal neutron energies, as well as across varying sample thicknesses. Additionally, secondary radiation effects were analyzed by quantifying the number and average energy of secondary neutrons and gamma photons generated from interactions with thermal and fast neutrons. Radiation damage parameters, including Total Ionizing Dose (TID) and Displacement Per Atom (DPA), were also evaluated. Gamma-ray shielding performance was assessed through experimental measurements, theoretical models, and Monte Carlo simulations, focusing on key parameters such as mass attenuation coefficients, kerma relative to air and concrete, and buildup factors. Among the composites, the sample labeled FeSTiB-50 demonstrated superior fast neutron attenuation capability-outperforming conventional concrete and approaching the shielding efficiency of paraffin-while all composites exhibited excellent attenuation of thermal neutrons. Furthermore, the FeSTiB-50 composite generated secondary radiation with lower average energy compared to other samples. However, the gamma-ray shielding performance was found to decrease with increasing TiB2 content, indicating a trade-off between neutron and gamma shielding effectiveness.
Keywords: FeSTiB composites; Shielding; GEANT4; Secondary radiation; Radiation damage